Metabolic Health, Insulin, and Breast Cancer: Why Oncologists Should Care About Insulin - Yee, Lisa D.; Mortimer, Joanne E.; Natarajan, Rama; Dietze, Eric C.; Seewaldt, Victoria L. (Frontiers in Endocrinology, 2020)
Studies investigating the potential link between pre-menopausal obesity (as measured by body mass index (BMI)) and breast cancer have been inconsistent. Recent studies show that BMI is not an exact measure of metabolic health; individuals can be obese (BMI >35 kg/m2) and metabolically healthy or lean (BMI <25 kg/m2) and metabolically unhealthy. Consequently, there is a need to better understand the molecular signaling pathways that might be activated in individuals that are metabolically unhealthy and how these signaling pathways may drive biologically aggressive breast cancer. One key driver of both type-2 diabetes and cancer is insulin. Insulin is a potent hormone that activates many pathways that drive aggressive breast cancer biology. Here we review 1) the controversial relationship between obesity and breast cancer, 2) the impact of insulin on organs, subcellular components, and cancer processes, 3) the potential link between insulin-signaling and cancer, and 4) consider time points during breast cancer prevention and treatment where insulin-signaling could be better controlled, with the ultimate goal of improving overall health, optimizing breast cancer prevention, and improving breast cancer survival.